STUDENTS' PERSPECTIVE AND EXPERIENCE ON THE USE OF ENGLISH AS MEDIUM OF INSTRUCTION IN INTRODUCTION TO BUSINESS CLASS: A QUALITATIVE INTERVIEW STUDY - Novel Doloksaribu; Debora Chaterin Simanjuntak (PROJECT (Professional Journal of English Education), 2021)
As higher education institutions strive to become increasingly international, English-medium teaching has become a main concern to develop students’ English proficiency in preparing them for international competition. Therefore, this study aims to investigate students’ perceptions and experience on a program called PEBUC. It is a program devised by the Faculty of Economy at Universitas Advent Indonesia (UNAI) in which the concept is derived from English Medium Instruction (EMI). It is a qualitative interview study, used to assess people’s experience, perceptions, behaviors and other aspects. Semi-structured interview was implemented to 10 informants who had experienced taking the program. The findings of this study showed two themes emerged on how students perceived the program; those themes are Promote Thinking-learning system and Stimulate Learners’ Engagement. Furthermore, there are two themes that characterize the experience of informants on the program; which are, Enhance recognition of English Language and Self-regulated learning. Meanwhile regarding the needs of program development there are two themes emerged: Learning Resources and Analysis on Students’ Prerequisites. All themes emerged from obtained sub-themes.